DNA fragmentation in complicated flow fields created by micro-funnel shapes. Issue 40 (27th September 2021) - Wu, Shuyi; Fu, Tengfei; Qiu, Renhui; Xu, Luping
Abstract : The significant effect of the micro-funnel shape on DNA fragmentation performance was systematically investigated by experiments and numerical simulations. Abstract : Micro-funnels have been widely applied to produce extensionally dominant flows for DNA manipulation, such as DNA extension for DNA mapping and DNA fragmentation for gene sequencing. However, it still lacks a systematic understanding of DNA fragmentation behaviors in complicated flow fields regulated by different funnel shapes with high flow rates. This limits the rational design and application scope of related microfluidic devices. In this study, fragmentation experiments of λ DNA were carried out in microfluidic chips with four different micro-funnel shapes, namely a sudden finish, a linear contraction, a constant acceleration, and an increasing extension rate funnel. The experimental results demonstrated a significant effect of the micro-funnel shape on the produced DNA fragment size. Then, the dynamical behaviors of DNA molecules in flow fields created by different micro-funnels were simulated using a numerical method of Brownian dynamics-computational fluid dynamics. The numerical simulation revealed that both the magnitude and distribution of the extension rate of flow fields were drastically altered by the funnel shape, and the extension rate at the micro-scale was the dominant factor of DNA fragmentation. The different DNA fragmentation behaviors in four micro-funnels were investigated from the perspectives including the fragment size distribution, fragmentation location, percentage of broken molecules, conformational type and stretched length of DNA before fragmentation. The results elucidated the significant impact of funnel shape on the dynamical behaviors of DNA fragmentation. This study offers insights into the rational design of microfluidic chips for DNA manipulation.